Eutrophication and nutrient release in urban areas of sub-Saharan Africa—a review - Nyenje, P.M.; Foppen, J.W.; Uhlenbrook, S.; Kulabako, R.; Muwanga, A. (Science of the total environment, 2010)
Eutrophication is an increasing problem in sub-Saharan Africa (SSA), and, as a result, the ecological integrity of surface waters becomes compromised, fish populations become extinct, toxic cyanobacteria blooms are abundant, and oxygen levels reduce. In this review we establish the relationship between eutrophication of fresh inland surface waters in SSA and the release of nutrients in their mega-cities. Monitoring reports indicate that the population of mega-cities in SSA is rapidly increasing, and so is the total amount of wastewater produced. Of the total amounts produced, at present, less than 30% is treated in sewage treatment plants, while the remainder is disposed of via onsite sanitation systems, eventually discharging their wastewater into groundwater. When related to the urban water balance of a number of SSA cities, the total amount of wastewater produced may be as high as 10–50% of the total precipitation entering these urban areas, which is considerable, especially since in most cases, precipitation is the most important, if not only the ‘wastewater diluting agent’ present. The most important knowledge gaps include: (1) the fate and transport mechanisms of nutrients (N and P) in soils and aquifers, or, conversely, the soil aquifer treatment characteristics of the regoliths, which cover a large part of SSA, (2) the effect of the episodic and largely uncontrolled removal of nutrients stored at urban surfaces by runoff from precipitation on nutrient budgets in adjacent lakes and rivers draining the urban areas, and (3) the hydrology and hydrogeology within the urban area, including surface water and groundwater flow patterns, transport velocities, dynamics of nutrient transport, and the presence of recharge and discharge areas. In order to make a start with managing this urban population-related eutrophication, many actions are required. As a first step, we suggest to start systematically researching the key areas identified above.
Keywords: SanitationNutrientsEutrophicationHydrologySlumsSub-Saharan Afric